(3GdfbhO h GdeUGQas - (3eMehO MSjf(B, (3GdhGOjs; (3MSjf eMeO(B, (3SeMGfs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2010)
(3ebOeI aj GdfbhO , GdfXe h GdfXQjGJ GdfbOjI , GdfbhO h GdeSJhi GdYGe ddGSYGQ , , GdfbhO aj GdGSdGe , GdHfhc GdJLGQjI , GdHfhc GdeQcRjI, GdHfhc GdGSdGejI , GdeDSSGJ GdeGdjI GdhSjWI GdGNQi (B.s
(3eQGLY U(B.229s
Keywords: (3GdGbJUGO GdeGdjs; (3GdHfhcs; (3GdeUGQas; (3GdfbhOs